2006
DOI: 10.1017/s0031182006001582
|View full text |Cite
|
Sign up to set email alerts
|

Direct characterization of Blastocystis from faeces by PCR and evidence of zoonotic potential

Abstract: In vitro propagation followed by PCR, and a PCR-based method capable of the direct detection of Blastocystis in faeces were utilized to detect Blastocystis from various hosts in Australia, including primates and their handlers from the Perth Zoo. In addition, Blastocystis isolates from dogs and humans living in a localized endemic community in Thailand were also characterized genetically. PCR-based detection directly from faeces was shown to be more sensitive compared with in vitro culture for the detection of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
148
3
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(169 citation statements)
references
References 44 publications
(61 reference statements)
9
148
3
6
Order By: Relevance
“…The results from this study, with PCR being the most effective form of diagnosis, are consistent with those of studies that reported that molecular analysis is the most efficient method for detection of Blastocystis . 12,23 This finding is in contrast to those of another study, 20 which suggested that in vitro culture was superior to direct PCR for stool samples.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…The results from this study, with PCR being the most effective form of diagnosis, are consistent with those of studies that reported that molecular analysis is the most efficient method for detection of Blastocystis . 12,23 This finding is in contrast to those of another study, 20 which suggested that in vitro culture was superior to direct PCR for stool samples.…”
Section: Discussioncontrasting
confidence: 76%
“…[10][11][12]23 In our study, two media, MBD and TYGM-9, were used for comparison of growth of Blastocystis in culture. These culture media were used instead of Jones medium because it was known that Blastocystis grows successfully in Jones medium.…”
Section: Discussionmentioning
confidence: 99%
“…The main rout of the transmission in humans is fecaloral, but molecular studies revealed that a zoonotic transmission can occur (11). Based on studies conducted on a genetic diversity using the small subunit rDNA (SSU-rDNA), at least 17 subtypes (STs) of Blastocystis were identified in humans and animals (2).…”
Section: Introductionmentioning
confidence: 99%
“…So far 17 subtypes have been identified within the Blastocystis clades existing in mammals, birds and reptiles. Due to recent studies it has been shown that no group exclusive to humans exists and that human isolates predominantly lie within subtype 1-4 [3][4][5]. Until recently, all human isolates of Blastocystis were commonly referred to as Blastocystis hominis and all other animal isolates were called Blastocystis sp.…”
Section: Introductionmentioning
confidence: 99%